Online retailing in Singapore : success or failure? - Ong, Ken Yong. (2008)
This research paper aims to find out the different factors that consumers consider when buying different products online. The products and services studied are: books, computers, financial services and travel services. The factors being tested are: security, price, brand, website and distribution.